Strategic Development of Indonesia’s Outermost Islands as an Enhancement of National Maritime Defense and Sovereignty - Muhammad Dzaki Fadhiil; Arie Afriansyah (Udayana Journal of Law and Culture, 2022)
The Republic of Indonesia as an archipelagic country has strategic territorial waters and a wealth of maritime resources. Indonesia's strategic position creates an area that has the outermost islands in the national border area. The outer islands of Indonesia are national natural resources to be utilized for their potential through the development of maritime resources. The huge potential of Indonesia's territory demands the development of the outer islands through economic improvement, investment, and tourism. The responsibility of the state in maximizing the potential of Indonesia's outermost region from a legal perspective is to maximize the determination of maritime boundaries in protecting the nation's sovereignty based on international law and national law. The article aims to analyze the projections of the Indonesian Government on the development of the outermost islands in strengthening maritime sovereignty as a form of anticipating violations of sovereignty. This paper argues that national defense maximizes and complements the implementation of the economy, investment, and tourism. Thus, the problem that arises is how the Indonesian Government's policy towards the development of the outermost islands is based on the aspect of national defense in increasing the economic, investment and tourism potential in the outer islands of Indonesia. The development of the outer islands is a holistic focus of the Indonesian Government in increasing economic potential, investment and tourism and ensuring national sovereignty through increasing national defense.